Modern Greek in Diaspora An Australian Perspective - Alvanoudi, Angeliki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book presents an in-depth fieldwork-based study of the Greek language spoken by immigrants in Cairns, Far North Queensland, Australia. The study analyzes language contact-induced changes and code switching patterns, by integrating perspectives from contact linguistics and interactional approaches to language use and code switching. Lexical and pragmatic borrowing, code mixing, discourse-related and participant-related code switching, and factors promoting language maintenance are among the topics covered in the book. The study brings to light original data from a speech community that has received no attention in the literature and sheds light on the variation of Greek spoken in diaspora. It will appeal across disciplines to scholars and students in linguistics, anthropology, sociology, and migration studies. Angeliki Alvanoudi is Lecturer at the Aristotle University of Thessaloniki, Greece, and Adjunct Lecturer at the Language and Culture Research Centre, James Cook University, Australia. She is the author of Grammatical Gender in Interaction: Cultural and Cognitive Aspects (2014) and has published articles in the journals Gender and Language and Journal of Greek Linguistics.
Chapter 1: Introduction -- Chapter 2: Borrowing and contact-induced change -- Chapter 3: Mixing codes -- Chapter 4: Conversational code switching -- Chapter 5: Participant-related code switching -- Chapter 6: What can we conclude?.
Keywords: Greek language; Linguistic change; Sociolinguistics; Multilingualism; Pragmatics; Emigration and immigration; Greek; Language Change; Sociolinguistics; Multilingualism; Pragmatics; Diaspora Studies